Pengaruh Upah Terhadap Produktivitas Kerja Karyawan - Sandi Fahrezi; Sudibyo BO Sudibyo BO (Journal of Innovation in Management, Accounting and Business, 2023)
A company is inseparable from employees who are directly involved in the company's operations. Employees are an important element in the company's operations, especially in increasing company productivity. Therefore, companies really need to pay attention to the welfare of employees by paying attention to their wages. This study aims to determine the effect of wages on employee work productivity at PT. Gemilang Inti Mandiri, Ligung District, Majalengka Regency. The type of research used is field research with a descriptive-qualitative approach. Respondents in this study were 100 employees who worked at PT. Gemilang Inti Mandiri. Collecting data using data collection methods, observation, interviews and documentation. The results of the study show that around 71.05% of employees are satisfied with the wages they receive. This percentage shows that the wages of employees are good. In addition, 72.91% of employees also showed good work productivity. Employees are committed and serious in carrying out their work. The capabilities and skills of employees at PT. Gemilang Inti Mandiri is also really well utilized. Employee motivation and enthusiasm are very visible when employees work. With the results of this study, the conclusion of this study is that wages affect employee work productivity.